Space as an element of economic security - Łuczyszyn, Andrzej; Chołodecka, Agnieszka (Przestrzeń jako element bezpieczeństwa ekonomicznego, 2015)
Shaping a safe space is an extremely complex and multi-faceted process. To large extent, it is based on the cooperation with various entities of the local community, participating in mutual interdependencies within local economies and above all, in the local socio-economic development. In modern realities, activity geared toward making changes in physical space and initiating programs to promote mobilization of society to improve safety takes on particular importance. Crime prevention strategies through shaping space are presented from the perspective of typical bodies which are to ensure safety and the local government as the main entity coordinating these processes in the local section. The article assumes the thesis that spatial conditions determine safety. The objective of this article is to show the importance of a safe space in the local context
Biblioteka Regionalisty, 2015, Nr 15, s. 63-72
Keywords: space; security; safety; local government; przestrzeń; bezpieczeństwo; samorząd